2D-dynamic representation of DNA sequences - Clark, Timothy; et al. (Chemical Physics Letters, 2007)
A new 'dynamic' 2D-graphical representation of DNA sequences is presented. The model is based on 2D-plots that have been used before and are easy to visualize, but it removes many degeneracies present in the previous approaches. The moments of inertia of the 'dynamic' graphs are proposed as a new kind of descriptor for DNA sequences. (C) 2007 Elsevier B.V. All rights reserved.